2021
DOI: 10.1097/bpb.0000000000000914
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular remodeling after graft extrusion, rotation or impaction in Dega and Pemberton acetabuloplasties for developmental dysplasia of the hip

Abstract: Traditionally graft displacement following Pemberton and Dega acetabuloplasties involves internal fixation for treatment of developmental dysplasia of hip (DDH). This study was performed to assess the acetabular remodeling by conservative management of graft displacement among patients with DDH. This was a retrospective study of 20 patients 17 (85%) women and 3 (15%) men; mean age 22.90 ± 6.96 months with DDH who underwent Pemberton and Dega acetabuloplasties at King Khalid University Hospital, Riyadh between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Out of 16 included studies, 7 studies [44,45,48,49,[51][52][53] reported follow-up data ranging from 3 and up to 49 months (Table 3). Adverse events have been observed in these 7…”
Section: Follow-up Data In Children Diagnosed With Ddh In Saudi Arabiamentioning
confidence: 99%
See 3 more Smart Citations
“…Out of 16 included studies, 7 studies [44,45,48,49,[51][52][53] reported follow-up data ranging from 3 and up to 49 months (Table 3). Adverse events have been observed in these 7…”
Section: Follow-up Data In Children Diagnosed With Ddh In Saudi Arabiamentioning
confidence: 99%
“…Out of these 58 studies, 26 were excluded, and 32 studies were retrieved for full-text review. Of these 32 studies for which full texts were reviewed, 16 were excluded (wrong outcomes/measures, n = 10; wrong patient population, n = 4; review study, n = 1; and case study, n = 1), and the remaining 16 studies were included in this systematic review study [38,39,[43][44][45][46][47][48][49][50][51][52][53][54][55], (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…[29][30][31] Furthermore, a recent study on graft displacement showed that similar radiologic outcomes could be achieved with spontaneous remodeling after a conservative approach. 32 Another complication that may occur due to medial wall disruption is triradiate cartilage injury. The most common radiographic findings of triradiate cartilage injury are widening or narrowing of the triradiate cartilage gap, bone bridge formation, triradiate cartilage ossification, and premature closure.…”
Section: Resultsmentioning
confidence: 99%